KrishiDrishti: Transforming Nepalese Farming into Precision Agriculture with Satellite and Digital Technology - Pandey, Shakriya; Chaulagain, Bidur P.; Thapa, Bikram; Pandey, Shrisha (Nepalese Journal of Agricultural Sciences, 2025)
Satellite remote sensing has emerged as a transformative tool in modern agriculture, providing real-time, large-scale, and cost-effective solutions to enhance both productivity and sustainability. This paper reviews the current applications of satellite data in agriculture, with a particular focus on its potential in Nepal. By examining global use cases in crop health monitoring, soil moisture estimation, weather pattern analysis, and land use classification, the paper emphasizes the value of integrating satellite technology into Nepal’s agricultural practices. It also explores the challenges of data accessibility, technical expertise, and policy integration, offering recommendations for overcoming these barriers to foster sustainable agricultural development. The paper introduces KrishiDrishti, a platform designed specifically for Nepal that uses satellite data to deliver actionable insights, empowering farmers and policymakers with tools for precision agriculture. By leveraging the potential of KrishiDrishti, this platform supports the transition to more efficient and climate-resilient farming practices, showcasing its transformative potential in Nepal’s agricultural sector.